In Vitro Assessment of Salivary Pellicle Disruption and Biofilm Removal on Titanium: Exploring the Role of Surface Hydrophobicity in Chemical Disinfection - Wenji Cai; Azam Fayezi Sisi; Mohamed‐Nur Abdallah; Ashwaq A. Al‐Hashedi; Juan Daniel Gamonal Sánchez; Enrique Bravo; Hasna H. Kunhipurayil; Rubens Albuquerque; Zahi Badran; Mariano Sanz; Faleh Tamimi (Clinical and Experimental Dental Research, 2025)
ABSTRACT Objectives Peri‐implantitis is mostly caused by a pathological biofilm that forms through complex processes, initiated by the formation of the salivary pellicle on implant surfaces. Understanding the nature of these pellicles and biofilm and how to remove them is important for preventing peri‐implant infections and improving the success of dental implants. This study explores the characteristics of the salivary pellicle on titanium surfaces and assesses the effectiveness of different decontamination agents in eliminating the salivary pellicle and related microbial contaminations. Materials and Methods Titanium surfaces were contaminated with salivary pellicles and pathological biofilms. The nature of the salivary pellicle was characterized using X‐ray photoelectron spectroscopy (XPS), surface proteomics, contact angle measurements, and fluorescence microscopy. We tested six commonly used decontamination chemicals (chlorhexidine, essential oil‐based mouthwash, citric acid, phosphoric acid, saline, and phosphate buffer saline) as well as newly proposed treatments such as surfactants and solvents (acetone, acetic acid, and Tween 20) for their capability to eliminate salivary pellicles and pathogenic biofilms from titanium surfaces. Results The hydrophobic nature of the salivary pellicle on titanium surfaces limits the efficacy of commonly used hydrophilic solutions in removing pellicles and bacteria. Organic solvents and surfactants, particularly acetic acid and Tween 20, demonstrated superior effectiveness in removing the pellicle and biofilm. Acetic acid was notably effective in restoring surface composition, reducing microbial levels, and removing multispecies biofilms. Conclusions The use of surfactants and solvents could be a promising alternative for the treatment of biofilms on titanium surfaces. However, further studies are needed to explore their clinical applicability.